2010
DOI: 10.1002/ptr.3186
|View full text |Cite
|
Sign up to set email alerts
|

Vitexin, orientin and other flavonoids from Spirodela polyrhiza inhibit adipogenesis in 3T3‐L1 cells

Abstract: To investigate the adipogenesis inhibitory effect on lipid accumulation, 3T3-L1 cells were treated with fractions and isolated flavonoids of Spirodela polyrhiza. An ethanol extract of S. polyrhiza was fractionated into three fractions. The butanol soluble fraction (SPB) exhibited potent antiadipogenesis activity and decreased C/EBPα and PPARγ protein expression level in 3T3-L1 cells without significant cytotoxicity. The flavonoids were isolated from SPB and their chemical structures were identified as chrysoer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
49
2
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 104 publications
(60 citation statements)
references
References 19 publications
(16 reference statements)
7
49
2
2
Order By: Relevance
“…The EtOAc and BuOH fractions were subjected to different column chromatography on Silica gel and Sephedex L-H-20 column led to the isolation of orientin from the EtOAc fraction and verbascoside from the BuOH fraction. The two compounds were identified by spectral analysis 1 H and 13 C-NMR (Tables 1 and 2) and compared with published data (Ismail et al, 1995;kim et al, 2010).…”
Section: Methodsmentioning
confidence: 99%
“…The EtOAc and BuOH fractions were subjected to different column chromatography on Silica gel and Sephedex L-H-20 column led to the isolation of orientin from the EtOAc fraction and verbascoside from the BuOH fraction. The two compounds were identified by spectral analysis 1 H and 13 C-NMR (Tables 1 and 2) and compared with published data (Ismail et al, 1995;kim et al, 2010).…”
Section: Methodsmentioning
confidence: 99%
“…Several clinical and animal studies have shown that phenolic compounds and carotenoids have a number of health benefits, including antiplatelet aggregation (Sheu et al, 2004), antiasthmatic (Jung et al, 2007), antioxidant (Liu et al, 2008), antiobesity (Kim et al, 2010), and antithyroid properties (Gaitan et al, 1989). Thus, although the germination rate of buckwheat seeds and the fresh weight of sprouts decreased at a high concentration of NaCl (200 mM), and we did not investigate the relationship between the accumulation of secondary metabolites and the functional properties of sprouts, our results suggest that NaCl treatment may represent an effective method to improve the nutritional quality of buckwheat sprouts, i.e., the level of phenolic compounds, carotenoids, and antioxidant activity.…”
Section: Effect Of Salinity Stress On Carotenoidsmentioning
confidence: 99%
“…To standardize GST, chlorogenic acid, vitexin, decursin, and torilin were used as surrogate markers and the content of each was quantified in GST samples (Ahn et al, 1996;Cho et al, 2008;Ge et al, 2007;Kim et al, 2010). Using high-performance liquid chromatography (HPLC), standardization of GST was carried out on a Waters system (Waters Corp., Milford, MA, USA), consisting of separation module (e2695) with a photodiode array detector (2998).…”
Section: Standardization Of Gstmentioning
confidence: 99%